2SPD-021 Survey of drug shortages in Hungarian hospitals. (24th March 2020) - Vida, RG; Sebők, S; Nyaka, B; Hornyák, J; Botz, L
Abstract : Background and importance: Drug shortages pose an enormous challenge to healthcare systems globally. However, the data available are limited, as there are 53 surveys in the literature and only 54.7% (29) contain any information regarding the prevalence of drug supply issues. Aim and objectives: Our aim was to develop a questionnaire based on the available surveys and collect evidence of drug shortages in Hungarian hospitals. Material and methods: With an extensive literature search between 1 and 15 April 2019, we identified the relevant surveys and questionnaires, and then developed a Hungarian version with 45 questions categorised into 5 main sections: (1) institutional data and demographics; (2) prevalence and background; (3) management of drug shortages; (4) information sources; and (5) consequences of drug shortages. Data were collected between 15 May and 30 June 2019, with an online survey among hospital pharmacists. Results: A total of 42 hospital pharmacist completed the survey: 36 women and 6 men, mainly >36 years of age (73.8%), from various institutions and scope of activities. We found that 52.4% experienced drug shortages more than 10 times in the past 6 months. The top five ATC groups included B (blood and blood forming organs (52.4%)), C (cardiovascular system (50%)), L (antineoplastic and immunomodulating agents (47.6%)), J (anti-infectives for systemic use (38.1%)) and N (nervous system (38.1%)). Active pharmaceutical ingredients highlighted were immunoglobulins, digoxin, sodium ferric gluconate, phytomenadione, idarubicin and amoxicillin/clavulanic acid. Original and generic drugs, and parenteral and oral dosage forms were equally affected. According to 53.7% of participants, drug shortage situations usually lasted for months. The main reasons noted were manufacturing problems (66.7%), tendering processes (54.8%) and raw material supply problems (52.4%). Serialisation was also mentioned (16%) as a cause of drug shortages. Conclusion and relevance: This is the first time a drug shortage survey focusing on Hungary has been completed. The data and tendencies collected were mainly in accordance with results of previous surveys and global tendencies. However, a new finding is that drugs belonging to ATC group B were affected the most by supply disruptions in Hungary. In addition, this is the first time that serialisation was linked with drug shortages in a survey. References and/or acknowledgements: No conflict of interest.